2020
DOI: 10.3390/ijms21145123
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Lysate Induces in Human Osteoblasts Resumption of Cell Proliferation and Activation of Pathways Relevant for Revascularization and Regeneration of Damaged Bone

Abstract: To understand the regenerative effect of platelet-released molecules in bone repair one should investigate the cascade of events involving the resident osteoblast population during the reconstructive process. Here the in vitro response of human osteoblasts to a platelet lysate (PL) stimulus is reported. Quiescent or very slow dividing osteoblasts showed a burst of proliferation after PL stimulation and returned to a none or very slow dividing condition when the PL was removed. PL stimulated osteoblasts maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, platelets activate STAT3, thus stimulating endothelial cells involved in angiogenesis and osteogenesis processes. These results corroborate the finding that, in regenerative medicine, platelets activate quiescent osteoblasts, while stimulating angiogenesis [ 10 ].…”
Section: Original Articlessupporting
confidence: 91%
“…Furthermore, platelets activate STAT3, thus stimulating endothelial cells involved in angiogenesis and osteogenesis processes. These results corroborate the finding that, in regenerative medicine, platelets activate quiescent osteoblasts, while stimulating angiogenesis [ 10 ].…”
Section: Original Articlessupporting
confidence: 91%
“…Quiescent or very slowly dividing osteoblasts showed a burst of proliferation after platelet stimulation and returned to a non-dividing or very slowly dividing condition when platelets were removed. Besides, freeze-dried PRP induced osteoblast proliferation via platelet-derived growth factor receptor- The red text means that the p value was < 0.05. mediated signal transduction (15). These studies demonstrated that platelet were strongly associated with bone formation.…”
Section: Discussionmentioning
confidence: 86%
“…Although the content of platelet lysates is highly promising for regenerative approaches in translational orthopedics [ 32 ] and these systems are also non-invasive (i. v. punction), they leave the surgical site and do not penetrate porous bone substitutes as a vacuum system can. At the very least, most systems designed for bone regeneration are at a pre-clinical stage [ 33 ].…”
Section: Introductionmentioning
confidence: 99%